Linear IFMIF Prototype Accelerator (LIPAc): Installation activities for Phase-B beam commissioning in Rokkasho. (May 2018) - Kondo, Keitaro; Ayala, Juan Marcos; Bolzon, Benoit; Cara, Philippe; Dzitko, Hervé; Ebisawa, Takashi; Fagotti, Enrico; Gex, Dominique; Heidinger, Roland; Hirata, Yosuke; Ichimiya, Ryo; Ikeda, Yukiharu; et al.
Highlights: The installation of Linear IFMIF Prototype Accelerator (LIPAc) is progressing. RFQ, MEBT and beam diagnostics are in line and ready for beam commissioning. RF power system is fully commissioned, and RFQ cavity has been conditioned. Abstract: The construction of the Linear IFMIF Prototype Accelerator (LIPAc) is in progress in order to demonstrate the feasibility of the low energy section of an IFMIF deuteron accelerator up to 9 MeV with a beam current of 125 mA in CW. The next milestone of the project is the so-called Phase-B beam commissioning, and one of the missions is to demonstrate the acceleration of the proton beam up to 2.5 MeV or the deuteron beam up to 5.0 MeV in pulsed mode with a low duty cycle of 0.1% through RFQ. Most of the components and subsystems necessary for Phase-B were delivered by 2016 under the responsibility of Fusion for Energy (F4E) as in-kind contributions of several European institutes, namely CEA (France), CIEMAT (Spain), INFN (Italy), and SCK-CEN (Belgium), and QST is in charge of the installation of the delivered equipment. The installation and check-out of the RFQ subsystem and the RF power system was completed by July 2017, and the RF conditioning of the RFQ cavity started. Also, the installation and the check-out of the important sub-systems for Phase-B, namely MEBT and beam diagnostics, have been completed.